PERBANDINGAN KEEFEKTIFAN MEDIA GAMBAR DAN MEDIA TEKS NARASI DALAM PEMBELAJARAN MENULIS GEGURITAN SEDERHANA PADA SISWA KELAS IX SMP 2 KUDUS - Kumudaningsih, Tri - (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2014)
The aim of this research is to explain the differences of learning writing of geguritan using picture media and narrative text media for students of classes IX SMP 2 Kudus from attitude aspect, knowledge aspect, and skill aspect. This study produced a description of the difference between picture media and narrative text media for learning writing geguritan of classes IX SMP 2 Kudus by observation, questionnaire, interview, and test which result that writing of geguritan using picture media and narrative text media from attitude aspect, knowledge aspect, and skill aspect have different and similarities. Learning of writing geguritan using picture media and narrative text media have their own strength. Both media have advantages and disadvantages of each so that each effective medium is used for learning to write geguritan with different circumstances. Keywords: writing, geguritan, media, picture, narrative text.